PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN TERHADAP TERDAKWA TINDAK PIDANA PENGHINAAN BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (Analisis Putusan Nomor 218/Pid.Sus/2020/PN.Pdg dan Putusan Nomor 356/Pid.Sus/2020/PN.Pdg) - Wami Irma Suryani (LPPM Universitas Ekasakti Padang, 2021)
The provisions of Article 27 paragraph (3) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions specifically regulates defamation or insults carried out by utilizing information technology through electronic media. Dissemination of electronic information containing pornographic content, fake news, defamation, insults is a type of criminal act that is actually the most prevalent in society. The Padang District Court on decision number: 218/Pid.Sus/2020/PN.Pdg and decision number: 356/Pid.Sus/2020/PN.Pdg handed down a different verdict against the defendant in the criminal act of humiliation.